Use of Learning Resources to Improve Learning Quality of Islamic Education in Madrasah Ibtidaiyah of Mutiara Bunda Surabaya - Nurul Fitriyah; Muhammad Hambal (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Use of learning resource in improving the quality of learning in Islamic Religious Education Subjects at Madrasah Ibtidaiyah (MI) in Mutiara Bunda Surabaya, Thesis of Islamic Education Study Program, Postgraduate Program, Muhammadiyah University of Surabaya. The research was motivated by educational problems, starting from the lack of enthusiasm for student learning, student apathy towards lessons, not conducive to the learning process and the rise of student online games. The formulation of the problem of this thesis, First, how to use learning resources in improving the quality of learning in Islamic Religious Education subjects in MI that was elementary school. Mutiara Bunda Surabaya. Second, how was the function of using learning resources in MI. Mutiara Bunda Surabaya. Third, what was the impact of the use of learning resources in MI. Mutiara Bunda Surabaya. This type of research was a field research that collected primary data through interviews with the deputy head of Madrasah, MI teachers and students in Mutiara Bunda. Secondary data was from literature and MI documents in Mutiara Bund. After all the data collected were analysed qualitatively, in descriptive form. The results were concluded that the use of appropriate and maximum learning resources can improve the quality of learning, namely first using modules or worksheets, libraries, internet, resource persons and the environment. The two functions of learning sources as sources of information were motivating, providing comprehensive experiences and instilling new concepts to students. The three impacts of using learning resources provided positive motivation and direct learning experiences. Supporting factors were policies of the principal of madrasah, motivation of teachers and families. Inhibiting factors were limited facilities and infrastructure, time, and low intention and motivation.